Pelatihan Soal-Soal Berpikir Komputasi Pada Mahasiswa Baru Pendidikan Matematika - Angraini, Lilis Marina; Kania, Nia (INCOME: Indonesian Journal of Community Service and Engagement, 2023)
Training on computational thinking questions for new Mathematics Education students is a training that aims to improve the understanding and computational thinking skills of students who are currently studying mathematics. Computational thinking is a key ability that allows individuals to formulate problems, develop algorithms, and apply computational concepts in problem solving. This training program identifies the gap between the ideal understanding of computing and today's reality, and seeks to fill the gap. Through a series of comprehensive training sessions, students are introduced to the basic concepts of computational thinking and the integration of mathematics with computing. They are given the opportunity to practice designing mathematical problems that require computational thinking as part of their teaching. This program aims to create mathematics teachers who are better prepared and competent in teaching mathematical concepts, while preparing them to face the demands of a world that is increasingly dependent on technology. In order to achieve this goal, this training emphasizes the importance of regular evaluations to monitor student progress. In this way, this training provides benefits for students in the context of mathematics education, but also contributes to the development of stronger mathematical literacy among the younger generation and their preparation for success in an increasingly digitally connected future.